2022
DOI: 10.3390/diagnostics12122964
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence, Wearables and Remote Monitoring for Heart Failure: Current and Future Applications

Abstract: Substantial milestones have been attained in the field of heart failure (HF) diagnostics and therapeutics in the past several years that have translated into decreased mortality but a paradoxical increase in HF-related hospitalizations. With increasing data digitalization and access, remote monitoring via wearables and implantables have the potential to transform ambulatory care workflow, with a particular focus on reducing HF hospitalizations. Additionally, artificial intelligence and machine learning (AI/ML)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Moreover, the authors of the review in ref. [17] showed that artificial intelligence and ML (AI/ML) in heart failure diagnostics and therapy can improve workflow and outcomes, especially for time series data collected via remote monitoring. However, limitations like data integration, privacy, and challenges in healthcare apply to AI/ML in wearable technology.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Moreover, the authors of the review in ref. [17] showed that artificial intelligence and ML (AI/ML) in heart failure diagnostics and therapy can improve workflow and outcomes, especially for time series data collected via remote monitoring. However, limitations like data integration, privacy, and challenges in healthcare apply to AI/ML in wearable technology.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The incorporation of device-related charges into healthcare insurance benefit packages is necessary in order to reduce the digital gap that is established based on economic disparities. In addition, loaner digital wearables have the potential to assist in offseting the financial effects on healthcare, provided that safeguards are in place to ensure that the digital gadgets are returned without any problems [ 202 ]. A lack of digital literacy can not only hinder the implementation of digital technology but also affect the degree to which patients comply with data transmission.…”
Section: Reviewmentioning
confidence: 99%
“…Machine learning techniques (often referred to as artificial intelligence) also enter the field of clinical prediction modeling of CHFS. The application of machine learning methods to CHFS syndrome is freshly reviewed in [115][116][117]. It has become an excellent practice to compare the efficiency of machine learning classifiers with the efficiency of established and well-researched logistic regression.…”
Section: Machine Learning Approachesmentioning
confidence: 99%